Музична культура Криму: національні особливості - Аблязімова, Е.А. (Культура народов Причерноморья, 2014)
У статті розглядаються поняття музичної культури в цілому, специфіка музичної культури
Криму в національному контексті, внесок певних художників у її становлення, особливості музичних
культур кримських татар, вірмен, караїмів, кримчаків і греків населяють півострів; взаємодія і
взаємопроникнення цих культур. Представлений ряд імен діячів музичної культури Криму: Ст.
Пасхалова, С. Майкапар, А. Рефатов, Я. Шерфедінов, Е. Налбандов, В. Бахшиш, М. Халітова, Е. Емір,
Д. Кариков, О.К. Глазунов, А А. Спендіаров. В статье рассматриваются понятия музыкальной культуры в целом, специфика
музыкальной культуры Крыма в национальном контексте, вклад определенных художников в ее
становление, особенности музыкальных культур крымских татар, армян, караимов, крымчаков и греков
населяющих полуостров; взаимодействие и взаимопроникновение этих культур. Представлен ряд имен
деятелей музыкальной культуры Крыма: В. Пасхалова, С. Майкапар, А. Рефатов, Я. Шерфединов,
Э. Налбандов, И. Бахшиш, М. Халитова, Э. Эмир, Д. Кариков, О.К. Глазунов, А.А. Спендиаров. The article examines the concept of musical culture in General, specifics of musical culture of the
Crimea in the national context, the contribution of certain artists in its development, peculiarities of musical
cultures of the Crimean Tatars, Armenians, Karaims, Krymchaks and Greeks living in the Peninsula; interaction
and interpenetration of these crops. Presents a number of names of musical culture figures of Crimea:
musicologist V. Paskhalova, the composer S. Maykapar, Crimean Tatar composer, conductor, teacher, music
and public figure, folklorist, scientist, ethnographer - A. Rafatov; Crimean Tatar composer, painter,
ethnographer, folklorist, the honored worker of arts of the Crimean ASSR and the Uzbek SSR - Ya. Sherfedinov;
composer, choirmaster, member of the Union of composers of Ukraine, member of the Union of composers of the
USSR, honored worker of culture of Uzbekistan, honored scientific worker of arts of Ukraine, State prize
laureate of AR Crimea E. Nalbandov; composer, teacher, member of Union of composers of Ukraine, honored
worker of art of the Crimean Autonomous Soviet socialist Republic, Honored worker of arts of Ukraine, honored
artist of Uzbekistan, laureate of State prize of Crimea – I. Bakhshish; composer, member of the Union of
composers of the USSR, member of the Union of composers of Ukraine, laureate of AR Crimea – M. Khalitova;
composer, member of the Union of composers of Ukraine, laureate of AR Crimea - E. Emir; the composer
D. Karikov; composers, students M.A. Rimsky-Korsakov O.K. Glazunov, A.A. Spendiarov.